Tweeting about the COVID-19 vaccine: A content analysis. - Hauer, Michael K; Jenkins, Alexander; MacPherson, Janna; Sun, Qingyue; Swain, Marianne (Atlantic Journal of Communication)
Twitter has been an influential and often controversial strategy for disseminating, discussing, and sharing information about the COVID-19 vaccine during the pandemic. This study focuses on using Twitter as a data collection and analysis tool to understand the narrative surrounding the COVID-19 vaccine in the days after the first emergency-use authorization (EUA). We conducted a content analysis of tweets we collected over a 30-day period (n = 419,495) and developed an iterative codebook that contained six domains (tweet source, location, tweet characteristics, COVID-19 specific topics, demographic descriptors, and sentiment) and thirty-six codes. Despite the abundance of misinformation on Twitter about the vaccine, we found that more tweets were positive than negative in tone and contained mostly reliable and up-to-date information about the vaccine. Most tweets came from individuals though many came from organizations. We found little discussion of demographic descriptors such as race/ethnicity, religion, or socioeconomic status, nor did we see discussion of misinformation or mask-wearing. Additionally, few tweets came from politicians or political organizations, and we found little talk of politics. This article contributes to the growing body of evidence of using Twitter to understand the narrative surrounding health topics during public health crises such as COVID-19.